ON SOME ASPECTS OF BIOLOGY OF PRIACANTHUS MACRACANTHUS (CUVIER) - Rao, T Appa (Indian Journal of Fisheries, 2011)
Analysis of stomach contents of Priacanthus macracanthus revealed thatcrustaceans and toleosts are the chief constiuents of food; Penaeus sp, Metapenaeussp and Solenocera sp being the most important items. From frequency distributionsof intraovarian eggs, spawning period seems to be from November to January.The ratio between males and females is not constant. Size frequency distributionshowed that the species grows at the rate of 10 mm per month.